The number of tourist arrivals, governance and their impact on threatened bird species: worldwide evidence - Habibullah, Muzafar Shah; Din, Badariah; Wei, Chong Choo; Tan, Siow Hooi (Academic Research Publishing Group, 2018)
The number of international tourist arrivals is crucial for the tourism sector. However, there are positive and negative sides of tourism. Unsustainable tourism will result in the destruction of the forest and consequently led to biodiversity loss. The great benefits of forest which is a home for a wide variety of animals and plants which help to stored carbon, preventing the risk of flood and drought to occur, influencing climate change, stabilizing soils as well as providing food and a place for the indigenous people to live. As long as these benefits are being concerned, the role of international community is needed to prevent them from any harm in the future. The government of both the developed and developing nations recognized the importance of sustainable biodiversity for the national ecosystem as well as to the global environment. In this study we also investigate the response of biodiversity loss (measured by the number of threatened bird species on six measures of governance: voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality, rule of law, and control of corruption. The OLS outcomes suggest that tourism exhibit positive relationship with biodiversity loss. On the other hand, the six governance indicators suggest that good governance reduces biodiversity loss. Our further analysis using quantile regression estimates suggest that tourism affect positively biodiversity loss for all quantiles (0.05 0.25 0.50 0.75 0.90 0.95); while governance affect negatively biodiversity loss only at certain quartiles. One main policy implication of this study is that sustainable tourism is important to mitigate biodiversity loss, and effort for biodiversity conservation is supported by this study.